He role of compositional strategies in ar art: from marker-based to markerless systems - Korotaieva, S.; Suprun, O. (ХНЕУ, 2026)
The aim of this study is to analyze the evolution of compositional strategies in AR art in relation to technological development from marker-based systems to markerless environments and to determine their influence on artistic language, perception, and interaction with the viewer.
Keywords: marker-based systems